Preseason assessment of anaerobic performance in elite soccer players: comparison of isokinetic and functional tests - Delvaux, F.; Schwartz, C.; Rodriguez, C.; Forthomme, B.; Kaux, J.-F.; Croisier, J.-L. (Sports Biomechanics, 2023)
Isokinetic and functional jump tests are frequently performed for assessing the physical qualities of soccer players during preseason. The purpose of this investigation was to explore, in an elite soccer players population, the relationships between isokinetic strength and functional jump performances. Thirty-eight professional soccer players were evaluated as follows: isokinetic knee assessment in concentric (CON) mode (60, 240°/s) for quadriceps and hamstrings, and in eccentric (ECC) mode for the hamstrings only (30°/s); one-leg hop tests for distance (single hop (SH), triple hop (TH) and triple crossover hop (TCH)); one-leg vertical jump tests (countermovement jump, drop jump). Players with a low bodyweight normalised (BWN) quadriceps (Q) strength (<2.71 Nm/kg) performed, for a majority of the measured variables, significantly reduced jump performances compared to the players with high BWN Q strength (>3.14 Nm/kg; p < 0.05). Greater bilateral differences between uninjured and past injured lower limbs were found with isokinetics (Q CON 60°/s (mean bilateral difference (MBD): 10.3%; p < 0.01), Q CON 240°/s (MBD: 9.9%; p < 0.05), H ECC 30°/s (MBD: 16.1%; p < 0.001) than with functional tests (MBD: 2 to 9%; p > 0.05. In conclusion, due to their complementary role and implications for performance, functional and isokinetic tests should be associated in a preseason soccer players assessment.